2013
DOI: 10.1016/j.bbapap.2013.01.010
|View full text |Cite
|
Sign up to set email alerts
|

FlgM proteins from different bacteria exhibit different structural characteristics

Abstract: Intrinsically disordered proteins (IDPs) are a unique class of proteins that do not require a stable structure for function. The importance of IDPs in many biological processes has been established but there remain unanswered questions about their evolution and conservation of their disordered state within a protein family. Our group has been studying the structural similarities among orthologous FlgM proteins, a model class of IDPs. We have previously shown that the FlgM protein from the thermophile Aquifex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The number of examples of partially disordered proteins involved in various biological processes is increasing. Among them, a partially disordered antisigma factor has been reported [49] . The antisigma factor FlgM binds to and inhibits the activity of σ28 directing the transcription of proteins involved in the bacterial flagellum formation.…”
Section: Discussionmentioning
confidence: 99%
“…The number of examples of partially disordered proteins involved in various biological processes is increasing. Among them, a partially disordered antisigma factor has been reported [49] . The antisigma factor FlgM binds to and inhibits the activity of σ28 directing the transcription of proteins involved in the bacterial flagellum formation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the corresponding thermophilic protein from Aquifex aeolicus has more secondary structure content (29) and the structure of its functional complex (PDB ID 1RP3) was determined by x-ray crystallography at 2.3 Å resolution (30). Further experimental studies of more FlgM proteins adapted at different temperatures revealed varying degrees of compactness and secondary structural content (31).…”
Section: Introductionmentioning
confidence: 97%
“…DisMeta analyzes a protein sequence using eight disorder prediction algorithms (DISEMBL, DISOPRED2, DISpro, FoldIndex, GlobPlot2, IUPred, RONN and VSL2). From each algorithm, disorder predictions are provided separately by the server, along with a plot showing the disorder levels of all amino acid residues in a protein sequence predicted by the algorithms 15 . In addition, protein sequence are also analyzed by seven sequence analysis tools (coils, ANCHOR, SignalP, TMHMM, SEG, PROFphd and PSIPred) to provide the information including secondary structure, binding site and complexity prediction 16 .…”
Section: Resultsmentioning
confidence: 99%